Earnings and Cash Flow Information on Its Value Relevance by The Book Value - Purbasari, Heppy; Bawono, Andy Dwi Bayu; Ramadhanti, Mila; Kurniawati, Lintang (Universitas Muhammadiyah Surakarta, 2020)
This study aims to examine the relationship of earnings and operating cash flow as an independent variable on the value relevance of accounting information proxied by stock returns by using book value as a moderating variable. The utilization of stock returns as an independent variable was selected as previous research on value relevance that tends to use stock prices as an independent variable. The sample of this study was all population of companies registered on the Jakarta Islamic Index (JII) in 2016-2018, JuneNovember period (issued from June 1st), by using saturation sampling. The data used in this study was compound from annual reports in the Indonesia Stock Exchange (IDX) and stock prices from Yahoo Finance. Further, data were tested using multiple linear regression analysis. The results showed that earnings and cash flow affect value relevance proxied by stock returns. However, book value neither strengthens nor weakens earnings and cash flow towards stock returns as a moderating variable.